Leisure Possibilities of Adults Experiencing Poverty: A Community-Based Participatory Study. (June 2022) - Cantor, Pamela; Polakowska, Monika; Proietti, Amanda; Tran, Victor; Lebire, Jonathan; Roy, Laurence
Background. Poverty disproportionally affects persons with disabilities, elderly individuals and racialized groups. Leisure, play and rest are not prioritized in either services for or research with people living in poverty.Purpose. This study aims to examine the facilitators and barriers to participation in meaningful leisure activities for adults living in poverty.Method. We used community-based participatory research and art-based elicitation strategies with 39 service users at a food security organization.Findings. Individuals experiencing poverty value and engage in a variety of free and affordable leisure activities, but they are not afforded the necessary leisure opportunities, accommodations and supports as the general population. We co-created a map of local leisure resources to foster collective capacity in leisure planning, and to support organizations working with this population.Implications. Occupational therapists can work alongside members of underserved communities to uncover and address the systemic and local contextual barriers to engagement in leisure activities.